2020
DOI: 10.3390/jcm9061678
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Cilostazol to Dual Antiplatelet Therapy to Enhance Mobilization of Endothelial Progenitor Cell in Patients with Acute Myocardial Infarction: A Randomized, Placebo-Controlled EPISODE Trial

Abstract: Background: Endothelial progenitor cells (EPCs) have the potential to protect against atherothrombotic event occurrences. There are no data to evaluate the impact of cilostazol on EPC levels in high-risk patients. Methods: We conducted a randomized, double-blind, placebo-controlled trial to assess the effect of adjunctive cilostazol on EPC mobilization and platelet reactivity in patients with acute myocardial infarction (AMI). Before discharge, patients undergoing percutaneous coronary intervention (PCI) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…58 A randomized controlled trial (RCT) in patients with acute myocardial infarction (MI) undergoing PCI, randomized to cilostazol SR (200 mg/day; n = 30) or placebo (n = 30) added to DAPT with clopidogrel and aspirin, indicated that patients with cilostazol had higher endothelial progenitor cell counts vs the placebo after 1 month. 59 Furthermore, the cilostazol group had decreased platelet reactivity. These findings attest to cilostazol's pleiotropic effects against atherothrombotic events.…”
Section: Cardiovascular Effectsmentioning
confidence: 97%
See 1 more Smart Citation
“…58 A randomized controlled trial (RCT) in patients with acute myocardial infarction (MI) undergoing PCI, randomized to cilostazol SR (200 mg/day; n = 30) or placebo (n = 30) added to DAPT with clopidogrel and aspirin, indicated that patients with cilostazol had higher endothelial progenitor cell counts vs the placebo after 1 month. 59 Furthermore, the cilostazol group had decreased platelet reactivity. These findings attest to cilostazol's pleiotropic effects against atherothrombotic events.…”
Section: Cardiovascular Effectsmentioning
confidence: 97%
“…Cilostazol also enhanced the mobilization of endothelial progenitor cells contributing to endothelial repair and improved endothelium‐dependent function by altering some metabolic and angiogenic markers in 71 patients at increased risk of CVD 58 . A randomized controlled trial (RCT) in patients with acute myocardial infarction (MI) undergoing PCI, randomized to cilostazol SR (200 mg/day; n = 30) or placebo (n = 30) added to DAPT with clopidogrel and aspirin, indicated that patients with cilostazol had higher endothelial progenitor cell counts vs the placebo after 1 month 59 . Furthermore, the cilostazol group had decreased platelet reactivity.…”
Section: Cardiovascular Effectsmentioning
confidence: 99%
“…Cilostazol may be beneficial in patients with VSA by virtue of its action of reducing the cytosolic calcium concentration, leading to vasodilation [7]. Cilostazol has antiplatelet properties which reduce the atherothrombotic burden in patient with coronary artery disease [8,9]. Previous data suggest that cilostazol is effective in patients with VSA who cannot tolerate conventional treatment [10,11].…”
Section: Introductionmentioning
confidence: 99%